E-Commerce Adoption and Growth of SMEs in Uganda - Wanzu, Ibrahim; Turyakira, Peter; Katumba, Proscovia M. (International Journal of Business and Management, 2019)
Information and communication technologies (ICT), particularly e-Commerce, are considered very important to the growth and competitiveness of businesses globally. SMEs too need to embrace innovative e-commerce strategies if they are to stay competitive, profitable and successful in local and global markets. Increased use of the Internet offers potential benefits to SMEs, such as cost reduction, improved operational efficiencies, access to new customers and enhanced business growth. However, SMEs, particularly in Uganda, have generally been slow in adopting e-commerce. Empirical research into the challenges SMEs in Uganda face in adopting electronic commerce is also limited. This study sought to explore the factors affecting e-commerce adoption among SMEs; and to establish the influence of e-commerce adoption on SMEs’ growth in Uganda. A structured, self-administered questionnaire was used to collect data from 172 owners/managers of SMEs in the Kampala District in Uganda. The empirical results of this study indicate that e-commerce adoption significantly influence the growth of SMEs.
Keywords: E-commerce adoption; Growth; Small and medium enterprises